Teachers’ Supervisory Strategies in Managing Students’ Online Gaming Habits and their Relationship to Academic Performance - Heducos, Jeneliza L.; Espia, Mark Joseph Q. (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study focused on the supervisory strategies employed by Junior and Senior High School teachers at Quezon National High School and how these strategies correlate with students’ tendencies to play online games and their academic performance. The study used a quantitative, descriptive-correlational approach and sampled 80 teachers. Data were collected using a validated survey designed by the researcher which assessed teachers’ supervisory strategies in the three areas of classroom management, motivational strategies, and support mechanisms, and their observation of students’ online gaming behaviors across the dimensions of frequency, intensity, and demonstrations of gaming behavior. The academic performance of students was evaluated based on the average of the second-quarter grades of the 2025-2026 School Year. The findings showed that teachers viewed their supervisory strategies to be effective with mean ratings in the “Strongly Agree” category except for the counseling and support mechanisms, which rated more neutrally. Teachers reported incidents of problematic online gaming behaviors exhibited by students that caused severe negative behavioral manifestations in the classroom, such as drowsiness, failure to meet deadlines, and lack of attention. Academic performance was rated “Satisfactory” across all the assessed grade levels (overall M=83.23), which means that there was no grade in that range exceeded that category and that there was a need to do better systematically. Despite large sizes, which typically indicate meaningful relationships, the correlation analysis for gaming behavior and academic performance (r= -.622) and supervisory strategies and academic performance (r= -.657) were not statistically significant (p > .05) in either case. Based on the findings, a Digital Supervision Plan anchored in the Transformational Leadership, Self-Regulated Learning, and Self-Determination theories is proposed to foster positive digital habits, improve self-regulation, and subsequently enhance academic performance within the school community.